2010
DOI: 10.1002/hlca.201000005
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acids as Mild and Effective Catalysts for the Synthesis of 3,5‐Bis[(hetero)arylidene]piperidin‐4‐ones

Abstract: The aldol-crotonic condensation reactions of N-alkyl-and NH-piperidin-4-one derivatives with (hetero)aromatic aldehydes promoted by Lewis acids or bases were examined. This comparative study has revealed three effective catalytic systems based on Lewis acids, i.e., LiClO 4 and MgBr 2 (in the presence of tertiary amine), and BF 3 · Et 2 O, for the synthesis of N-alkyl-substituted 3,5-bis(heteroarylidene)piperidin-4-ones, including those bearing acid-or base-labile groups both in the (hetero)aromatic groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…IR spectra were recorded in KBr pellets on a Magna‐IR750 (Nicolet, Madison, WI) Fourier spectrometer, resolution 2 cm −1 , 128 scans. The starting 3,5‐bis(arylidene)piperid‐4‐ones 1a–e and compounds 2 and 3 were prepared according to the known procedures, and their chemical–physical characteristics fit well with the literature data. All reagents and solvents used were obtained from Aldrich (St. Louis, MO) and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…IR spectra were recorded in KBr pellets on a Magna‐IR750 (Nicolet, Madison, WI) Fourier spectrometer, resolution 2 cm −1 , 128 scans. The starting 3,5‐bis(arylidene)piperid‐4‐ones 1a–e and compounds 2 and 3 were prepared according to the known procedures, and their chemical–physical characteristics fit well with the literature data. All reagents and solvents used were obtained from Aldrich (St. Louis, MO) and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Piperidine is a naturally occurring bioactive alkaloid (Hu et al, 2002;Finke et al, 2001;Taniguchi & Ogasawara, 2000) and the heterocyclic six-membered nitrogen-containing piperidine ring is an essential structural part of many important drugs including paroxetine, raloxifene, haloperidol, droperidol and minoxidiln (Wagstaff et al, 2002). 2,6-Diphenyl-substituted piperdine-4-one derivatives are important because of their potential biological activities such as antitumor, antimicrobial, analgesic, local anesthetic, antidepressant and anti-inflammatory (Ká lai et al, 2011;Leonova et al, 2010;El-Subbagh et al, 2000;Jerom & Spencer, 1988). This wide range of biological activities prompted us to synthesize novel 2,6-diphenyl piperdine-4-one derivatives with enhanced biological activities.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Anna examined passivation behavior of Type 304L stainless steel in methanol containing 0.1 kmol m −3 LiClO 4 and reported that the passivation was not attained when the water content was less than 500 ppm. 27 As the electrolyte could be acidic because LiClO 4 is also a Lewis acid, 28 it was considered that a relatively large amount of water molecules were required for passivation. On the other hand, EMI-TFSI is not subjected to the hydrolysis reaction and is Lewis neutral, leading to the situation where no Lewis acids were present in the vicinity of the sample surface.…”
Section: Impaired Repassivaion Of Type 304 Stainless Steel In Water-f...mentioning
confidence: 99%